A single‐arm pilot of a web‐based intervention to improve itch‐related quality of life. (5th October 2021) - Heckman, C.J.; Riley, M.; Niu, Z.; Lu, S.‐E.; Valdes‐Rodriguez, R.; Yosipovitch, G.
Abstract: Background: Many patients with chronic itch and atopic dermatitis (AD) or psoriasis do not receive/use available medical and psychosocial treatments properly due to system, provider and/or patient factors. Objective: An educational website (ITCH‐RELIEF) to improve itch‐related quality of life (QoL) for adults with AD or psoriasis and chronic itch was developed and assessed. ITCH RELIEF stands for Interactive Toolbox of Comprehensive Health Resources to Enhance Living with Itch – Educational Facilitation (for Adults). Methods: Single‐arm pre‐ and post‐test design with 1‐month follow‐up ( N  = 137 at baseline). Results: There was statistically and clinically significant improvement in the primary outcome of itch‐related QoL impairment as assessed by the ItchyQoL from baseline [ M  = 78.9, 95% confidence interval (CI) = 75.9, 81.9] to follow up ( M  = 75.4, CI = 72.4, 78.5), P  = 0.007, as well as statistically significant improvement in several itch‐related secondary outcomes (all P s < 0.05). Conclusions: This study demonstrated initial effectiveness of an online intervention to improve itch‐related QoL among individuals with AD or psoriasis and chronic itch. Future studies should address limitations by randomizing more heterogeneous participants, utilizing a longer follow‐up and assessing medication use.